2021
DOI: 10.1080/09538259.2020.1861817
|View full text |Cite
|
Sign up to set email alerts
|

Infection Is the Cycle: Unemployment, Output and Economic Policies in the COVID-19 Pandemic

Abstract: This paper seeks to capture the dynamic interaction between the epidemiological evolution of COVID-19 and its effect on the macroeconomy, in absence of widespread vaccination. We do that by building a stylized two-equations dynamical system in the COVID-19 positivity rate and the unemployment rate. The solution of the system makes the case for an endemic equilibrium of COVID-19 infections, thus producing waves in the two variables in the absence of widespread immunity through vaccination. Furthermore, we model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…For example, Barrot et al (2020) estimate that a 10% increase in state-level labour restrictions in the US led to a 3% drop in employment and a 1.87% drop in the market value of firms in April 2020 alone. The unemployment rate in this period was the highest in American history, at 14.7% (BLS, 2021;Goes & Gallo, 2021). It is a very similar increase in the unemployment rate as was estimated in our study in Slovakia, although these are very different countries.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Barrot et al (2020) estimate that a 10% increase in state-level labour restrictions in the US led to a 3% drop in employment and a 1.87% drop in the market value of firms in April 2020 alone. The unemployment rate in this period was the highest in American history, at 14.7% (BLS, 2021;Goes & Gallo, 2021). It is a very similar increase in the unemployment rate as was estimated in our study in Slovakia, although these are very different countries.…”
Section: Discussionsupporting
confidence: 85%
“…To this end, countries have taken the strategy such as closing borders, blocking global personnel flow to prevent the spread of novel coronavirus. This is a short-term emergency measure for long-term economic development [2]. Although, after a while, international trade slowly recovered, but the more crisis occurred at home.…”
Section: Causes Of the Global Unemploymentmentioning
confidence: 99%
“…In view of the current situation of the labor market, such as highly inactive economic activities, increasing long-term unemployment and employment inequality, it should be emphasized that it is not only necessary to extend unemployment benefits, but also urgently need to take major policy intervention to meet the total demand, especially for low-income groups. In the research of Maria, Barbieri and Gallo, they found that the current stimulus policy and the maintenance of aggregate demand in the United States play a key role in preventing the labor market fluctuations caused by the repeated pandemic waves, while reducing the negative impact of unemployment on GDP [2].…”
Section: Solutions To Unemploymentmentioning
confidence: 99%
“…Constructing a two‐equation dynamical system of COVID‐19 positivity rate and the unemployment rate, Barbieri‐Góes and Gallo (2021) capture the evolution of COVID‐19 and its effects on the economy. They get both endemic‐free and endemic equilibria, whereas the endemic equilibrium, as they suggest, is more realistic.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of extensive vaccination, the endemic equilibrium causes pandemic‐driven waves in the unemployment rate. Barbieri‐Góes and Gallo (2021) then simulate the unemployment shock on the overall level of economic activity and find that the shock causes negative effect on the output level. Moreover, in the absence of adequate stimulus policies, the emergence of cyclical downswings may determine an L‐shaped recession in the medium run.…”
Section: Introductionmentioning
confidence: 99%